Avalanche charge generation in anhydrous glucosides excited by an external electric field - Sugimura, Akihiko; Iwamoto, Mitsumasa; Hashim, Rauzah (American Institute of Physics, 2019)
Glycolipids are components of cellular membranes comprising a hydrophobic lipid tail and one or more hydrophilic sugar heads, and are widely associated with the fields of life science and biochemistry. Due to the hygroscopic nature of sugar, the dry thermotropic phases of glycolipids have fewer studies. We report on the electric charge generation in anhydrous glucosides excited by the external high electric field (∼2 MV/m). This causes a large current in the smectic A phase, but not in the isotropic phase. Its intensity is about 100 times larger than the steady state current. The generation of the current was found to be irreversible by the repetition of the field application. The large electric carrier generation is originated in the smectic A phase, possibly due to an electron avalanche breakdown mechanism caused by the collisions of electrons through the impact ionization. © 2019 Author(s).